Penyelesaian Sengketa Non Litigasi Dalam Penyelesaian Sengketa Perdata - Ni Made Trisna Dewi (Jurnal Analisis Hukum, 2022)
The judiciary is basically formed to try and solve problems, but in reality sometimes it is not able to solve the problems faced by the parties, sometimes even causing new problems, namely prolonged hostility between the disputing parties. The problems that will be discussed in this research are What are the legal remedies for non-litigation settlement in dispute resolution according to civil law?, and what are the obstacles to resolving non-litigation disputes according to civil law? The research method used is an empirical research method that is guided by data collection techniques with direct interviews with competent people using peace theory, effectiveness theory in the rule of law concept to study and get answers to existing problems. The results of this study are legal efforts to resolve disputes over buying and selling diamonds in civil law cases, namely by non-litigation, this is generally done in civil cases only because it is more private in nature by having several forms to resolve disputes, namely: Negotiation, Mediation and Arbitration. Meanwhile, the obstacles to non-litigation settlement in the settlement of civil law cases of buying and selling are juridical barriers regarding mediation and the validity of the results of the peace where the parties sometimes or the public doubts the final outcome of dispute resolution through mediation and non-juridical barriers, namely obstacles that occur because the parties involved directly related to the diamond sale and purchase dispute, prioritizing emotions in problem solving. The emotional factor with its arrogance assumes that all parties are in the right position, so they don't want to give up.